Wendy, darling - Wise, A. C. (Titan Books, 2021)
"Find the second star from the right, and fly straight on 'til morning, all the way to Neverland, a children's paradise with no rules, no adults, only endless adventure and enchanted forests - all led by the charismatic boy who will never grow old. But Wendy Darling grew up. She has a husband and a young daughter called Jane, a life in London. But one night, after all these years, Peter Pan returns. Wendy finds him outside her daughter's window, looking to claim a new mother for his Lost Boys. But instead of Wendy, he takes Jane. Now a grown woman, a mother, a patient and a survivor, Wendy must follow Peter back to Neverland to rescue her daughter and finally face the darkness at the heart of the island..."--